Urgensi Implementasi Green Ekonomy terhadap Pemeliharaan Jiwa Manusia (Hifz Nafs) Perspektif Al-Qur’an: The Urgency of Implementing Green Economy towards the Preservation of the Human Soul (Hifz Nafs) from the Perspective of The Qur’an - Fatmawati, Fatmawati; Achmad Abubakar; Sohrah, Sohrah; Heri Iswandi (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2025)
This study aims to analyze how the urgency of implementing the green economy on the maintenance of the human soul (Hifz Nafs) perspektif al quran. This research is a qualitative study by conducting library research. The data in the study was obtained by conducting content analysis of sources that have relevance to the topic of research conducted. The results of the study indicate that the importance of implementing the green economy concept in the economy is First, in general, environmental damage that occurs comes from economic activities carried out by individuals in households and by industry. Second, environmental maintenance is part of maintaining human survival (hifz Nafs), and environmental damage is a threat to human survival. Third, the concept of green economy is in line with the goals of the Indonesian national economy as stated in the Constitution Article 33 paragraph 4. Fourth, in the Koran it is clearly stated that the purpose of humans being created was as caliphs who were responsible for making the earth prosperous, not vice versa.